100k views
1 vote
Let f(x) = x2 and g(x) = x − 3. Evaluate (f ∘ g)(−2).

2 Answers

3 votes
F(g(-2))
F(-2-3)
F(-5)
25
User Chibani
by
7.1k points
4 votes

Answer: f (g (-2)) = 25

Explanation:

Hi, to evaluate (f ∘ g)(−2). Where:

f(x) = x2

g(x) = x − 3

As (f ∘ g)(−2) = f (g (-2))

First we find the value of g (-2) replacing the variable x by the number -2.

g (-2) =-2-3 = -5

Finally , for f(x) = x²,we replace the variable x for the value obtained (-5)

f (g (-2)) = (-5)²= 25

Feel free to ask for more if needed or if you did not understand something.

User Splynx
by
8.1k points